Ocean and Coastal Resources Components and their Contributions to Sustainable Development of Nigeria - J. N. Osuji; J. Agbakwuru (Journal of Applied Sciences and Environmental Management, 2024)
The blue economy, which encompasses the sustainable use of ocean resources for economic growth, has the potential to revolutionize Nigeria's maritime industry and provide a significant boost to the country's economy. The subject has been taken seriously in recent time in many parts of the world basically due to the sustainability it implies to the use of ocean in boosting national and therefore well-being of the people. Hence, the objectives of this paper were to examine ten important blue economic components and evaluate their contributions to the sustainable development of Nigeria using various secondary data acquisition. Data obtained reveals that out of the ten (10) blue economic components studied, oil/gas exploration, maritime transport/shipping and fisheries dominate the blue economic contributions with the oil/gas exploration contributing 90% of the blue economic value in Nigeria. This work has shown that efforts are required both from the government and private sectors to pursue the huge opportunities available especially in the non-oil/gas exploration components to sustainably improve the economic base of the nation and generate huge employment opportunities for the large growing Nigerian population.